Enhancing Citizen Participation for Development in Tanzania - Abel Kinyondo; Riccardo Pelizzo (Otoritas : Jurnal Ilmu Pemerintahan, 2019)
The literature has repeatedly emphasized that citizen participation is requisite for good governance. Indeed, when citizens participate in various public activities, they can voice their demands, they can invite the government to respond to their demands, and they can keep government accountable. In other words, in the presence of citizen engagement activities, voices can be raised to governments accountable. While the literature has clearly established this link, less is known about the levels of citizen engagement in rural areas in developing countries like Tanzania; precisely areas where good governance is most needed to secure some progress along the developmental path and take the population out of poverty. Using an original dataset comprising of 1,265 respondents, we find that citizen participation in rural Tanzania varies across various types of activities. We also find that that the participation rate for men is higher than that of women and that the participation rate for older people is higher than it is for younger ones. Given the fact that Tanzania’s population is largely youthful, and women are slightly more than men, we recommend for the removal of barriers that women and youths face as far as their civic rights to participate in developmental activities is concerned.